Variation in Linguistic Complexity and Human Ratings of Second Language (L2) Writing - Trinh, Thanh (International Journal of English Language and Pedagogy, 2025)
Drawn upon the usage-based approach which considers inter-individual variation as an inherent feature of language use and production, this study attempted to explore what linguistic complexity measures significantly differed among individual learners of similar learning conditions and how they were compatible with rubric-based scorings. Statistical analyses confirm that variation in complexity ranged from lexical, syntactic to discoursal levels. Comparisons with human ratings reveal that the variation in linguistic complexity measures is complex in nature since complexity correlates with perceived proficiency, particularly when it comes to semantic cohesion and lexical control but in others, complexity varies independently of performance, suggesting that the developmental stage of complexity may moderate its impact on ratings.